Fatores individuais e contextuais associados à incapacidade em idosos brasileiros - Danielle Samara Tavares de Oliveira Figueirêdo (2019)
The relation between chronic diseases and disability is well established, but few studies propose to analyse the independent effects of simultaneous individual and contextual factors and the occurrence of disability in the elderly population. Objective: To analyse the association of individual factors (gender, schooling, social networking and access to health services) and contextual determinants (socioeconomic indicators of the States of the Federation) with the inability to instrumental and basic activities in Brazilian elderly population. Methods: A cross-sectional study using data from 11,177 elderly participants of the National Health Survey (NHS) in 2013. The variable outcome was the disability, measured by five instrumental activities of daily living (IADLs) and seven basic activities (ADLs). The exposures were: sex, schooling, characteristics of the social network and access to health services and contextual indicators (average Gross Domestic Product per capita between 2002 and 2012 by States Unity (SU), Gini Index t of 2012 by SU and average per capita household income of 2012 and Sociodemographic Index by SU of 2013). Descriptive analyses and multiple and multilevel logistic regression models were performed, adjusted for confounding factors, considering a significance level of 5%. Results: The prevalence of disability for IADL was 28.0% (95% CI: 26.7-29.4) and for ADL was 15.5% (95%CI: 14.4-16.6). Women were more likely to have difficulties with IADL, but not for ADL. The lower schooling, the greater the chances of disability. Women who do not live with their partner (OR = 1.89; 95%CI: 1.50-2.37); who do not participate in social activities (adjusted OR = 1.88,95%CI: 1.48-2.39) and do not perform any voluntary work (adjusted OR 1.81,95%CI: 1.16-2.82) or paid work (adjusted OR = 3.36,95% CI: 2.26-4.98) showed higher odds of disability in IADL. Among men, the ones that do not practice social activities and not working were associated with disability in IADL, after adjustment. The proportion of elderly people with problems to access health services was 4.72% (95% CI: 4.11-5.43) and those who are more prone to disability. The variance of the probability of disability in IADL among the SU was σu2 = 0.0485 (95%CI: 0.024-0.096; p <0.001) and, for ADL, σu2 = 0.0363 (95%CI: 0.015-0.087; p < 0.001). Rio Grande do Sul, São Paulo, Rondônia, Santa Catarina, Federal District, Espírito Santo, and Rio de Janeiro had a lower chance of occurrence of disability to IADL. Sergipe, Amazonas, Rio Grande do Norte, Ceará, Alagoas, and Piauí presented a higher chance for IADL in the elderly population. Only Alagoas had a greater chance of disability for ADL. The Gini Index reduced the variance of the SUs of Brazil to the probability of disability in IADL in 80.3%. For ADL, GDP per capita decreased by 77,6%. Conclusion: Female population are more likely to be incapacitated than males in the early stages of functional decline. Low schooling and lack of social network are associated with disabilities. Having problems accessing health services can increase the chances of disability. More socioeconomically unequal states such as those in the North and Northeast Region require improvements in social and health policies for the promotion of active aging and maintenance of functionality.